An Analysis of Internal Control Effectiveness in Improving Accounts Payable Payment Accuracy at the St. Regis Bali Resort - Ni Ayu Komang Ariwati; Titien Damayanti; I Putu Arnawa (Jurnal Multidisiplin Sahombu, 2025)
The hospitality industry faces challenges in maintaining the accuracy of accounts payable payments due to the high volume of transactions and the complexity of financial procedures. This study aims to analyze the effectiveness of internal control in improving the accuracy of accounts payable payments at The St. Regis Bali Resort. By using descriptive qualitative research methods through interviews, observations, and documentation, data was obtained from the accounts payable department and related departments. The results showed that although the hotel had implemented internal controls based on the COSO framework, there were still weaknesses in the form of lack of document verification, delayed payments, and weak separation of duties. This condition has an impact on the risk of recording errors and decreasing the reliability of financial statements. The study concluded that the internal control system was not fully effective in ensuring the accuracy of accounts payable payments. The implication is that management needs to strengthen the separation of functions, integrate financial information systems, and improve interdepartmental coordination to minimize the risk of errors and improve relationships with suppliers. The findings provide a practical contribution for hotel management in improving the financial system as well as adding to the academic literature related to internal control in the hospitality industry